A Multipulse Pattern Modulation Scheme for Harmonic Mitigation in Three-Phase Multimotor Drives - Davari, P.; Yang, Y.; Zare, Firuz; Blaabjerg, F. (2016)
© 2013 IEEE. A continuous improvement of power electronics technology has widely increased the applications of adjustable speed motor drives in many areas. Beyond the control flexibility, the power electronics devices (e.g., diode rectifiers) are also the main harmonic source to the grid due to their nonlinearity, which thus deteriorates the power grid quality and also lowers the conversion efficiency. Both degradations are apt to occur in motor drive applications. At present, many industrial drives are equipped with three-phase diode rectifiers and employ passive filtering techniques on the ac or the dc side of the rectifier. In such topologies, it is difficult to implement the prior-Art harmonic control strategies. Moreover, the total cost and complexity has become the main obstacle for these harmonic elimination approaches in multiple drive systems. Therefore, in this paper, a new cost-effective harmonic mitigation approach has been proposed for multiple drives. The proposed approach can control the generated current harmonics by benefiting of the nonlinearity of the drive units and through a novel current modulation scheme. The obtained results at the simulation and the experimental level validate the effectiveness of the proposed approach.